Review of Orman, Jon (2008). Language Policy and Nation-Building in Post-Apartheid South Africa. - (:unkn) unknown (My University, 2009)
Orman's book documents language policy in South Africa from (mostly) the standpoint of the history of Afrikaans and the political position of the language. I argue that African languages deserve more consideration for the topic to be treated in its entirety.
Keywords: African Research